Learner Responsibility and Homework Quality in Secondary EFL Blending (Training and Practice : Journal of Educational Sciences, 2017)
The purpose of this research is to scrutinise advantages and disadvantages of blended learning both from the perspective of the learners and the teacher in a secondary EFL class. Throughout the four-week blending process, online and offline content being the same, informants did their homework through Macmillan Online Campus. Based on weekly learner feedback, an interview with the mentor teacher and post-lesson reflections of the teacher-researcher the study concluded by saying that blending results in learner awareness of higher quality homework, however does not necessarily raise learner awareness and learner responsibility. Disadvantages and advantages of MEC were also elaborated on both from the teacher’s and the learners’ perspective.